A RESEARCH STUDY INVESTIGATING HOW LEARNERS PROCESS TEXT, AUDIO, AND PICTURES (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
In contemporary educational settings, learners are increasingly exposed to information through multiple modes such as written text, audio materials, and visual images. The integration of digital technologies into education has significantly changed the way knowledge is delivered and processed. This research study investigates how learners process text, audio, and pictures, and examines the cognitive mechanisms involved in multimodal learning. The study is grounded in cognitive learning theories and aims to explore the effectiveness of each mode of input as well as their combined use. Understanding these processes is essential for designing effective instructional materials and improving learning outcomes.